Influence of haylage type of feeding on some physico-chemical properties of milk of high-yielding dairy cows - L.A. Khujanova; B. Djambilov; F. Jurakulov (Genius Journals, 2021)
The biometric examination of the physico-chemical parameters of milk from German Holstein cows fed as haylage is presented in this paper. It has been found that maintaining imported cows under nutritious feeding circumstances helps to generate a high-quality dairy product during the adaptation period.
Keywords: Shivery Acidity; Lactase; Consistency; Analog